Community Assistance in Pulau Bulang in Tourism Marketing through Social Media and Digital Platforms for the Promotion of Cultural Heritage and Mangrove Ecotourism - Wardani, Yudha; Nensi Lapotulo; I Wayan Thariqy Kawakibi Pristiwasa; Haufi Sukmamedian (JURNAL KEKER WISATA, 2026)
This community service program aims to enhance the capacity of the Pulau Bulang community in tourism marketing through social media and digital platforms for the promotion of cultural heritage and mangrove ecotourism. Pulau Bulang possesses significant natural and cultural tourism potential; however, limited digital literacy and inadequate tourism marketing strategies have constrained its visibility and development as a sustainable tourism destination. The program was implemented using a participatory and community-based approach, involving local community members, youth groups, and tourism-related stakeholders. The activities were conducted through a series of mentoring sessions, interactive discussions, and hands-on practices focusing on digital content creation, social media utilization, and basic destination branding. Participants were guided to directly apply digital marketing concepts by producing and sharing tourism-related content that highlights local cultural heritage and mangrove ecosystems. Evaluation was carried out through observation, participant feedback, and assessment of digital outputs produced during the program. The results indicate an improvement in community awareness and skills in utilizing digital platforms for tourism promotion. Participants demonstrated increased confidence and ability to promote Pulau Bulang as a tourism destination in a more structured and sustainable manner. This program contributes to strengthening community participation in tourism development and supports sustainable tourism principles through the integration of environmental conservation, cultural preservation, and digital-based promotion strategies.